2019
DOI: 10.18632/aging.102193
|View full text |Cite
|
Sign up to set email alerts
|

Sodium cantharidate targets STAT3 and abrogates EGFR inhibitor resistance in osteosarcoma

Abstract: Osteosarcoma is the most common primary malignant bone tumor in children and adolescents. Overactive EGFR signaling is frequently seen in osteosarcoma cells, and represents a potential therapeutic target. However, feedback activation of STAT3 after EGFR inhibition is linked to treatment resistance, suggesting that combined EGFR/STAT3 inhibition may be needed to overcome this effect. Cantharidin and its analogues have shown strong anticancer effects, including STAT3 inhibition, in several tumor cells. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…4A ). Abnormal activation of STAT3 in tumor cells ensures the survival of malignant cells under stress conditions and also leads to multi-drug resistance ( 24 ). Erlotinib did not reduce the higher levels of STAT3 phosphorylation in HCC827ER cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A ). Abnormal activation of STAT3 in tumor cells ensures the survival of malignant cells under stress conditions and also leads to multi-drug resistance ( 24 ). Erlotinib did not reduce the higher levels of STAT3 phosphorylation in HCC827ER cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a number of studies showed that OS cells had resistance to EGFR inhibitors and the resistance could be overcome by combination with other treatment. Ji et al demonstrated that combined EGFR/STAT3 inhibition could overcome resistance of EGFR inhibition [ 45 ]. In another study, Gvozdenovic et al found that co-targeting of IGF-IR and EGFR signaling was a useful therapeutic strategy to overcome resistance EGFR inhibitors in OS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of AMBRA1 is associated with prognosis of bile duct cancer and cutaneous melanoma [58,59]. Xiang et al [60] showed that abnormal expression of EGFR is related to drug resistance in tumor patients. Chu et al [61] showed that PEX3 is related to the invasion and metastasis of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%